Global regional and national burden of cataract attributable to high body mass index from 1990 to 2019 - Xiaowen Lan; Baodong Zhang; Yuxi Ding (BMJ Open)
Objectives In order to estimate long-term trends of the years lived with disability (YLDs) for cataract due to high body mass index (BMI).Design and participants Data were retrieved from the Global Burden of Disease (GBD) 2019. The global cases, age-standardised rates (ASR) of YLDs for cataract attributable to high BMI were described by age, sex, geographical location and sociodemographic index (SDI). The estimated average annual percentage change (AAPC) was analysed to quantify the trends of ASR of YLD from 1990 to 2019.Primary outcome measures Years lived with disability.Results Globally, there were 370.4 (95% UI: 163.2 to 689.3) YLDs due to cataract attributed to high BMI in 2019, more than triple the number in 1990. Moreover, the ASR of YLD increased during 1990–2019, with AAPC of 1.54 (95% CI: 1.41 to 1.66). In 2019, the burden of cataract due to high BMI was higher in females and the elderly population. North Africa and the Middle East were the high-risk areas of cataract attributable to high BMI in 2019, with Saudi Arabia being the country with the heaviest burden. In terms of SDI, low-middle SDI regions had the greatest number of cataract-related YLDs due to high BMI in 2019.Conclusion The global YLDs for cataract due to high BMI have shown a notable increase from 1990 to 2019. Addressing BMI control may contribute to cataract prevention, highlighting a potential public health impact, particularly in low-SDI locations and among the elderly.